2008
DOI: 10.1007/s11606-008-0687-9
|View full text |Cite
|
Sign up to set email alerts
|

Classifying and Predicting Errors of Inpatient Medication Reconciliation

Abstract: Unintentional medication discrepancies are common and more often due to errors taking an accurate medication history than errors reconciling this history with patient orders. Focusing on accurate medication histories, on potential medication errors at discharge, and on identifying high-risk patients for more intensive interventions may improve medication safety during and after hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

23
319
4
11

Year Published

2009
2009
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 337 publications
(357 citation statements)
references
References 22 publications
23
319
4
11
Order By: Relevance
“…1,3,12,14,15,23,25 Several factors we found to be associated with medication reconciliation errors, such as older age and number of preadmission medications, were confirmed by others. 11,12,14,15 However, in one study fewer unintentional medication discrepancies were associated with age over 85 compared to age less than 50. 12 Herrero-Herrero et al found that the number of preadmission medications predicted unjustified discrepancies (i.e.…”
Section: Discussionsupporting
confidence: 76%
See 4 more Smart Citations
“…1,3,12,14,15,23,25 Several factors we found to be associated with medication reconciliation errors, such as older age and number of preadmission medications, were confirmed by others. 11,12,14,15 However, in one study fewer unintentional medication discrepancies were associated with age over 85 compared to age less than 50. 12 Herrero-Herrero et al found that the number of preadmission medications predicted unjustified discrepancies (i.e.…”
Section: Discussionsupporting
confidence: 76%
“…26 Furthermore, Pippins et al showed that 72% of all potentially harmful discrepancies in admission or discharge orders were due to PAML errors. 12 Similarly, we discovered that PAML errors and medication changes made during hospitalization predicted discharge medication errors.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations